2010
DOI: 10.5194/acp-10-3915-2010
|View full text |Cite
|
Sign up to set email alerts
|

Vertically-resolved particle size distribution within and above the mixing layer over the Milan metropolitan area

Abstract: Abstract. Vertical aerosol profiles were directly measured over the city of Milan during three years (2005)(2006)(2007)(2008) of field campaigns. An optical particle counter, a portable meteorological station and a miniaturized cascade impactor were deployed on a tethered balloon. More than 300 vertical profiles were measured, both in winter and summer, mainly in conditions of clear, dry skies.The mixing height was determined from the observed vertical aerosol concentration gradient, and from potential tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 66 publications
10
74
0
Order By: Relevance
“…Although some studies have suggested that coherence exists among the various methods, most of the research was conducted in clear sky conditions (Kim et al, 2007;Ferrero et al, 2011Ferrero et al, , 2010McGrath-Spangler and Denning, 2013). We suggest that the presence of clouds is an important factor that reduces the agreement of different methods.…”
Section: Reasons For Discrepancies Among Different Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies have suggested that coherence exists among the various methods, most of the research was conducted in clear sky conditions (Kim et al, 2007;Ferrero et al, 2011Ferrero et al, , 2010McGrath-Spangler and Denning, 2013). We suggest that the presence of clouds is an important factor that reduces the agreement of different methods.…”
Section: Reasons For Discrepancies Among Different Methodsmentioning
confidence: 99%
“…Water vapour acts as a tracer of the atmospheric dispersion state which contains and integrates the effects of physical atmospheric forces (both thermal and mechanical) on substance dispersion (Ferrero et al, 2010). The h can be estimated as the level of the minimum vertical gradient of relative humidity (h RH ) or specific humidity (h q ) with a significant reduction in atmospheric moisture (Ao et al, 2008;Seidel et al, 2010).…”
Section: Comparison Of the Existing Methods To Determine Hmentioning
confidence: 99%
See 1 more Smart Citation
“…The pNO − 3 formation via N 2 O 5 uptake contributes to the gradients in the compound percentage and size distribution of the particle (Ferrero et al, 2010(Ferrero et al, , 2012. On nights when NO 3 cannot accumulate in the surface layer owing to high NO emissions, N 2 O 5 uptake can still be active aloft without NO titration.…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential impact of aerosols on climate, additional accurate measurements of the vertical profiles of aerosol optical properties are needed. These data can be obtained directly or indirectly from platforms such as meteorological towers (Zhao et al, 2017), tethered balloons (Stratmann et al, 2003;Ferrero et al, 2010), and unmanned aerial vehicles (Corrigan et al, 2008). Although limited in terms of temporal and geographic coverage, airborne sensing provides direct, highresolution, in situ aerosol vertical profiles, used to evaluate numerical models and satellite retrievals (Chazette and Liousse, 2001).…”
Section: Introductionmentioning
confidence: 99%